MAQASHID SYARI’AH DALAM HADIS WALIMAH ‘URS - Zul Ikromi; Tasnim Rahman Fitra (Islamic Civil Law Departement of Shari'a Faculty at Islamic State University of Sultan Maulana Hasanuddin Banten, 2023)
The orders and implementation of walimah are found in various hadiths of the Prophet, among the most famous hadiths is the hadith of awlim even though it is bi asy-syatin. The influence of the global world and modernization has given its own style to the implementation of weddings in the Islamic world, including Indonesia. Many things are found in the community related to shifts and deviations from the Sunnah of the wedding ceremony. Based on this fact, it is necessary to reveal the provisions of walimah contained in the hadith of the Prophet Muhammad, so that the khittah walimah can return according to the true syar`i guidance. This study uses a discriminatory-analytic method which aims to describe and reveal maqashid aspects in the hadith walimatul 'urs. This study reveals that the implementation law of walimatul `urs is a sunnah muakkat according to the majority of scholars, walimah al-'urs is highly recommended as one of the symbols of Islam, and as a means of notification to the public so as not to cause slander. Walimah al-'urs becomes syi'ar when complying with the provisions of Islamic law. The blessing of walimah al-'urs lies in its implementation which emphasizes the concept of simplicity with the meaning of using and removing all forms of accommodation according to needs and avoiding the existence of riya motives that lead to waste and useless actions.